Características clínico - quirúrgicos del vólvulo de sigmoides en pacientes atendidos en el Hospital Regional de Loreto enero 2015 agosto 2018 - Vela Fachin, Harry Hernan (2022)
GENERAL OBJECTIVE: To determine the clinical and surgical characteristics of Sigmoid Volvulus in patients treated surgically in the Surgery Service of the Regional Hospital of Loreto during the period from January 2015 to August 2018. MATERIALS AND METHODS: The methodology is qualitative because they are collected and Data is analyzed and interpreted through instruments designed for a specific purpose, Observational. Because it aims to establish the workings that exist between the concepts or variables, in a particular, descriptive context. Because it describes certain characteristics of a particular situation, Transversal. Because it performs the measurement (s) at a certain point of time, the study population was represented by the total clinical history of patients diagnosed with surgery for sigmoid volvulus, which according to the respective information, corresponded to 21 cases, between January and December of 2020.CONCLUSIONS: Intestinal obstruction produced by sigmoid colon volvulus is one of the most frequent surgical emergencies in Andean hospitals in Peru, several factors interact for the formation of a sigmoid volvulus, which can be divided into necessary factors , predisposing factors and precipitating factors, in addition the symptoms are those of an acute intestinal obstruction since patients present distension of the abdomen, nausea and vomiting, these symptoms rapidly progress to generalized pain and hypersensitivity of the abdomen, fever and leukocytosis and indicate gangrene, perforation, or both. The bases of initial non-surgical treatment are abdominal decompression, by evacuating the proximal intraluminal content and repositioning the colonic rotation on its axis to restore enteral blood circulation, while emergency surgical treatment should be guided by the general condition of the patient. patient and the state of the loop in the surgical act. To decide the technique to perform, the general conditions of the patient and the local conditions of the colon are of great importance.